"Unpresidented!" or: What happens when the president attacks the federal judiciary on Twitter. Issue 1 (2nd January 2021) - Kromphardt, Christopher D.; Salamone, Michael F.
ABSTRACT: There are many things that make Donald Trump a controversial figure in American politics, not least of which is his prominent and unorthodox use of Twitter to attack his opponents. The federal judiciary is a frequent target of the president's ire: during his campaign and tenure as president, Trump has not hid his disdain for federal judges who disagree with him, and has on occasion taken to Twitter to express these feelings. This unprecedented form of going public provides the opportunity to shed light on the malleability of support for politically insulated institutions. We evaluate the hypothesis that Trump's statements erode specific and diffuse support for the federal judiciary using a survey experiment in which real tweets written by the president are manipulated as the experimental treatment. We find that specifice, but not diffuse, support for the Court changes in response to his attacks, but those changes are conditioned on respondents' preexisting support for democratic values.